2015
DOI: 10.1007/s13344-015-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the hydrodynamic characteristics of biofouled full-scale net cage

Abstract: The effect of biofouling on the hydrodynamic characteristics of the net cage is of particular interest as biofouled nettings can significantly reduce flow of well-oxygenated water reaching the stocked fish. For computational efficiency, the porous-media fluid model is proposed to simulate flow through the biofouled plane net and full-scale net cage. The porous coefficients of the porous-media fluid model can be determined from the quadratic-function relationship between the hydrodynamic forces on a plane net a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Governing equations review In the present numerical model, the governing equations comprises the Navier-Stokes equations coupled with the realizable k-ε model, wh ich have been described in details in our previous studies (Bi, Zhao, & Dong, 2015;Zhao et al, 2013), thus a brief review is given here. Navier-Stokes equation are…”
Section: Description Of Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Governing equations review In the present numerical model, the governing equations comprises the Navier-Stokes equations coupled with the realizable k-ε model, wh ich have been described in details in our previous studies (Bi, Zhao, & Dong, 2015;Zhao et al, 2013), thus a brief review is given here. Navier-Stokes equation are…”
Section: Description Of Numerical Modelmentioning
confidence: 99%
“…As the most part of the float collar is above the free surface of the water and the sinkers and mooring system are relatively small-scale co mponents. Thus, only the netting is simu lated in this numerical model and the cylindrical netting is divided into 16 plane nets around the circu mference and one bottom net (Bi et al, 2015). Both the clean and biofouled netting of the net cage were simu lated using the porous -media flu id model and the corresponding porous coefficients were determined fro m the hydrodynamic forces acting on the plane-net sheet which are correlated with the features of the biofouled netting (Bi et al, 2015;Zhao et al, 2013).…”
Section: Description Of Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They created models of twines with artificial hydroid fouling and tested drag forces in a towing tank. Bi et al (2015); Bi et al (2017) studied the hydrodynamic characteristics of a single offshore net cage and a square array of offshore net cages with biofouling using a three-dimensional CFD model. They found that the damping effects of the cage array increased with increasing biofouling.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the cutoff would suppress the small eddies and, presumably, lead to drag reduction. Several researchers conducted a comprehensive study on drag reduction for water flow and proposed relationships for the Fanning friction factor, which helps other researchers to analyze their results [16][17][18][19]. Virk [20] investigated the performance of different polymer solutions and found a trend to a maximum drag reduction (MDR) asymptote in all cases.…”
Section: Introductionmentioning
confidence: 99%